Life without end a thought experiment in literature from Swift to Houellebecq - Guthke, Karl Siegfried 1933- (Camden House, 2017)
The idea of earthly immortality has a tradition in literature dating to the Gilgamesh epic. But what would it mean to attain such immortality? Answers are suggested in novels and plays that explore the theme using varieties of Borges's "rational imagination," often in connection with projections of biology or cybernetics. In this groundbreaking study, Karl S. Guthke examines key works in this vein, throwing into relief fascinating instances of human self-awareness across the last 300 years. Authors discussed in detail include J. M. Barrie, Calvino, Shaw, Adolfo Bioy Casares, Swift, Aldous Huxley, Walter Besant, Arthur C. Clarke, Wilde, Borges, William Godwin and other English Romantics, Capek, Machado de Assis, de Beauvoir, Martin Amis, Dino Buzzati, Houellebecq, Iris Barry, Saramago, Rushdie, Gabi Gleichmann, and Pascal Mercier. Guthke finds that the fictional triumph over death is only rarely viewed positively, and mostly as a "curse"-for a variety of reasons. Almost always, however, literary experiments with immortality suggest an alternative: the chance to take our limited lifetime into our own hands, shaping it meaningfully and thereby experiencing "a new way of being in the world" (Mercier). The fictional immortals reject this challenge, thus depriving themselves of what makes humans human and life worth living. And what that might be is also at least hinted at in the works Guthke analyzes. As a result, an aspect of cultural history comes into view that is revealing and stimulating at a time that is, as Der Spiegel put it in 2014, "obsessed by the invention of immortality." Karl S. Guthke is the Kuno Francke Professor of Germanic Art and Culture, Emeritus, of Harvard University